Soft grid integration control strategy for self synchronized voltage source DFIG wind turbine generator - Haoshu Shao; Qiang Dong; Zenglu Song; Yong Wang (Scientific Reports)
Abstract Transitioning to a power system heavily reliant on renewable wind energy involves more than just replacing conventional fossil-fuel-based power plant with wind farms, the wind energy must be able to meet the requirement of voltage establishment and power balance. It is believed that the self synchronized voltage source control of DFIG wind turbine generator is one of the possible solutions to realize virtual inertia and is helpful to increase the frequency stability of power system, thus is meaningful in the transformation of the power system dominated by renewable energy. Plenty of research has been conducted on the self synchronized voltage source control strategy in steady state, but few research is focused on the soft grid integration, which is a complicated process involving wind turbine control and power converter control. This paper proposes a novel soft grid integration control strategy for self synchronized voltage source wind turbine generator, including the mechanical start-up and electrical start-up process, with the coordination of pre-synchronization control of DFIG rotor side converter and grid side converter, the integration current of DFIG WTG can be significantly reduced. The effectiveness of proposed soft grid integration control strategy is verified on Real-time Digital Simulator.